2010
DOI: 10.1021/nn103082k
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Electrical Transport through Annealed Monolayers of Monodisperse Cobalt−Platinum Nanoparticles

Abstract: We synthesized monodisperse cobalt-platinum nanoparticles Co(0.14-0.22)Pt(0.86-0.78) of 9 nm in diameter by colloidal chemistry methods and deposited them by the Langmuir-Blodgett technique as highly ordered monolayers onto substrates with e-beam defined gold electrodes. Upon annealing we observe an increase of conductivity over more than 4 orders of magnitude. A first attempt of explanation of this unanticipated effect, a nanoparticle displacement, could not be confirmed for annealing temperatures below 400 °… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 35 publications
0
28
0
Order By: Relevance
“…Although many research efforts have been devoted to investigate the Coulomb charging energy in nanoparticle assemblies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], discrepancies still exist about some fundamental questions. One example is about the estimation of the Coulomb charging energy in nanoparticle assemblies.…”
mentioning
confidence: 99%
“…Although many research efforts have been devoted to investigate the Coulomb charging energy in nanoparticle assemblies [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30], discrepancies still exist about some fundamental questions. One example is about the estimation of the Coulomb charging energy in nanoparticle assemblies.…”
mentioning
confidence: 99%
“…The electric response of the network depends strongly upon the electrode distance. This occurs because certain physical properties like the overall contact resistance, the percolation threshold, the static energetic disorder of hopping sites , and the coupling to the environment change dramatically with array size. For the 50‐nm (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, it has been shown that the most ordered and large area arrays of MNPs 3 can be assembled on water surface [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The process involves deposition of evaporative solution of MNPs on a water surface where it spreads out to form a colloidal solution film.…”
Section: Introductionmentioning
confidence: 99%
“…Providing sufficient resolution for study nano-objects they, in addition, probe large area sample surfaces due to a large beam spread resulting from a very shallow angle of incidence. Assemblies of MNPs on solid substrates were intensively studied by means of grazing incidence X-ray reflectivity (XRR) and small-angle X-ray scattering (GISAXS) 12,13,16,17,27,31,35,37,38 , neutron reflectivity (NR) and grazing incidence small-angle neutron scattering (GISANS) 17 In the present study, for the first time, to our knowledge, a unique combination of in-situ GISAXS and XRR techniques, accompanied by the pressure-area isotherm analysis, BAM and ex-situ SEM were applied for investigation of super-lattices of magnetic nano-particles as they form directly on water surface in a Langmuir trough. Size and value of the magnetic 5 …”
Section: Introductionmentioning
confidence: 99%